Evaluation of brain CT-scan results and indications before lumbar puncture in children suspected of meningitis hospitalized in Ardabil city hospital - Vafaie, Majid; Mirzarahimi, Mehrdad; Enteshari-Moghaddam-moghaddam, Afsaneh; Mousavi, Sahar (International Surgery Journal, 2018)
Background: Multiple use of CT scan is associated with an increased risk of cancer in the future especially in children due to cellular growth and mutation. The aim of this study was to evaluate the result and indications of brain CT scan before lumber puncture in children with suspected of meningitis. Methods: In this retrospective cross-sectional study, information of brain CT Scans on all meningitis suspected children under 12 years old hospitalized in Ardabil city hospital at 2016 who were candidates of CT Scan before Lumbar Puncture were extracted and the results were analyzed by statistical methods in SPSS version 22. Results: In this study, a total number of 67 patients were studied and CT scan changes were seen in 13 cases (19.4%) that of them 6 (46.2%) were male and rest of them were female. The mean age of the cases that had CT scan changes was 36.9±2.14 months and in other patients were 38.8±3.56 months. Of all patients, 13 patients experienced decrease in consciousness level that CT scan changes were observed in 8 cases (61.5%). Of the 13 patients (19.4%) had CT scan changes, 5 (38.4%) ha brain structural lesions. Conclusions: The prevalence rate of CT-scan changes was 19.4% and the most commonly detections in patients by CT scan, were structural disorder of the brain and subdural effusion.